2023
DOI: 10.1139/cjas-2021-0122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quercetin supplementation on growth performance, nutrient digestibility, excreta bacterial count, noxious gas emission, and meat quality of broilers when fed different protein diets

Abstract: This study aimed to evaluate the effect of flavonoid supplementation to a low protein diet on growth performance, nutrient digestibility, excreta bacterial count and excreta gas emission of broilers. In total 800 one-day-old, Ross 308 broilers (BW; 42.90±1.43 g) were randomly sorted into one of the four dietary treatments (10 pens/treatment; 20 birds/pen). Treatment diets were HCP (High protein diet), basal diet; LCP (Low protein diet), basal diet – 2.5% protein; TRT1, LCP + 0.025% quercetin; TRT2, LCP + 0.050… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Broilers' apparent gastrointestinal absorption of DM and N retention were both improved by the plant‐derived compounds (Bafundo et al, 2021). Hoque and Kim (2023) demonstrated that the increasing amount of flavonoid inclusion demonstrated a trend of gradual improvement in DM digestibility while presenting no effect on nitrogen and energy retention (Hoque and Kim, 2023). They explained that the improved nutrient digestibility is related to the digestive enzyme activity, improved feed intake and intestinal health status of the broilers which may be the possible reason of increased digestibility in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Broilers' apparent gastrointestinal absorption of DM and N retention were both improved by the plant‐derived compounds (Bafundo et al, 2021). Hoque and Kim (2023) demonstrated that the increasing amount of flavonoid inclusion demonstrated a trend of gradual improvement in DM digestibility while presenting no effect on nitrogen and energy retention (Hoque and Kim, 2023). They explained that the improved nutrient digestibility is related to the digestive enzyme activity, improved feed intake and intestinal health status of the broilers which may be the possible reason of increased digestibility in our study.…”
Section: Discussionmentioning
confidence: 99%